Influence of job demands on implicit absenteeism in Chinese nurses: mediating effects of work–family conflict and job embeddedness - Yujie Zhang; Shanyan Lei; Liying Chen; Fang Yang (Frontiers in Psychology, 2023)
PurposeIt has been widely noted that implicit absenteeism is common among nurses, with job demand influencing it. Theoretically, work–family conflict and job embeddedness may help link job demands to implicit absenteeism. However, the mediating effects of the two on the association between job demands and implicit absenteeism remain unclear. Thus, this study aims to explore the association between nurses’ job demands and implicit absenteeism, and the chain mediating effect of work–family conflict and job embeddedness in this relationship.Patients and methodsData were collected from 1,420 nurses from five tertiary public hospitals in China. They were asked to respond to a questionnaire asking about job demands, implicit absenteeism, work–family conflict, and job embeddedness. The data were coded and analyzed using IBM SPSS version 21.0. Descriptive analysis, t-test, one-way ANOVA, hierarchical multiple regression analysis, and bootstrapping were used to analyze the extracted data.ResultsThe mean score for implicit absenteeism was 17.75 ± 5.60. There was a significant correlation (p < 0.05) between nurses’ job demands, work–family conflict, job embeddedness, and implicit absenteeism. Nurses’ job demands directly influenced implicit absenteeism and indirectly influenced implicit absenteeism through the mediating effects of work–family conflict and job embeddedness. Furthermore, work–family conflict and job embeddedness have a chain effect on the association between job demands and implicit absenteeism.ConclusionThe study found that nurses’ job demands directly and positively influence implicit absenteeism, and indirectly influence implicit absenteeism through single and chain mediating effects of work–family conflict and job embeddedness.